A thermophysical and dynamical study of the Hildas, (1162) Larissa, and (1911) Schubart. Issue 4 (4th February 2021) - Chavez, Cristian F; Müller, T G; Marshall, J P; Horner, J; Drass, H; Carter, B
ABSTRACT: The Hilda asteroids are among the least studied populations in the asteroid belt, despite their potential importance as markers of Jupiter's migration in the early Solar system. We present new mid-infrared observations of two notable Hildas, (1162) Larissa, and (1911) Schubart, obtained using the Faint Object infraRed CAmera for the SOFIA Telescope (FORCAST), and use these to characterize their thermal inertia and physical properties. For (1162) Larissa, we obtain an effective diameter of 46.5$^{+2.3}_{-1.7}$  km, an albedo of 0.12 ± 0.02, and a thermal inertia of 15$^{+10}_{-8}$ Jm −2  s 1/2  K −1 . In addition, our Larissa thermal measurements are well matched with an ellipsoidal shape with an axial ratio a / b = 1.2 for the most-likely spin properties. Our modelling of (1911) Schubart is not as refined, but the thermal data point towards a high-obliquity spin-pole, with a best fit a / b = 1.3 ellipsoidal shape. This spin-shape solution is yielding a diameter of 72$^{+3}_{-4}$ km, an albedo of 0.039± 0.02, and a thermal inertia below 30 Jm −2  s 1/2  K −1 (or 10$^{+20}_{-5}$ Jm −2  s 1/2  K −1 ). As with (1162) Larissa, our results suggest that (1911) Schubart is aspherical, and likely elongated in shape. Detailed dynamical simulations of the two Hildas reveal that both exhibit strong dynamical stability, behaviour that suggests that they are primordial, rather than captured objects. The differences in their albedos, along with their divergent taxonomical classification, suggests that despite their common origin, the two have experienced markedly different histories.